Semi Cascade Dam Operation for Flood Control at Pacal Dam and Gongseng Dam - Zahari, Renalvin; Sobriyah, Sobriyah; Hadiani, Rintis (Newinera Publisher, 2025)
The existing condition of the Pacal Dam is experiencing swallowing due to sedimentation, resulting in a reduction in storage capacity.The construction of the Gongseng Dam is a solution to this problem.Pacal Dam and Gongseng Dam are semi-cascade dams whose management is an integration of different rivers. Hydrological analysis was carried out to obtain the Inflow hydrograph using the Nakayasu HSS Method using the discharge value at a 500-year return period (Q500). To determine the optimal capacity in flood control, a simulation of the operation of the Pacal Dam gate was carried out using the Level Pool Routing method on each dam. There are four scenarios simulated in the operation of the Pacal Dam spillway gate, namely the gate is completely closed (scenario 1), the gate is opened 50% (scenario 2), the gate is opened 75% (scenario 3), and the gate is fully opened (scenario 4). The simulation results show that in scenario 1 the Pacal dam is not safe, with a maximum outflow discharge value of 72.12 m3/dt with a water level above the spillway of 6.16. In scenarios 2, 3, and 4, the outflow discharge value is 80.39 m3/dt, 113,49 m3/dt, 143,62 m3/dt with water height above the spillway of 2.68 m, 2.37 m, 2.14 m. The results of the simulation of the operation of scenarios 1, 2, 3, and 4 of the Gongseng Dam routing are safe with a maximum outflow discharge value of 260.15 m3/dt, 280,89 m3/dt, 297,90 m3/dt, 319, 38 m3/dt and water height of 1.98 m, 2.08 m, 2.16 m, 2.27 mon spillway landmark. The best scenario is scenario 4 considering the height of the guard water on the spillway.